Leishmania braziliensis: Strain-Specific Modulation of Phagosome Maturation - da Silva Vieira, Tamara; Arango Duque, Guillermo; Ory, Kévin; Gontijo, Celia Maria; Soares, Rodrigo Pedro; Descoteaux, Albert (Frontiers in Cellular and Infection Microbiology, 2019)
Leishmania (Viannia) braziliensis is responsible for the largest number of American tegumentary leishmaniasis in Brazil (ATL). ATL can present several clinical forms including typical (TL) and atypical (AL) cutaneous and mucocutaneous (ML) lesions. To identify parasite and host factors potentially associated with these diverse clinical manifestations, we first surveyed the expression of two virulence-associated glycoconjugates, lipophosphoglycan (LPG) and the metalloprotease GP63 by a panel of promastigotes of L. braziliensis strains isolated from patients with different clinical manifestations of ATL and from the sand fly vector. We observed a diversity of expression patterns for both LPG and GP63, which may be related to strain-specific polymorphisms. Interestingly, we noted that GP63 activity varies from strain to strain, including the ability to cleave host cell molecules. We next evaluated the ability of promastigotes from these L. braziliensis strains to modulate phagolysosome biogenesis in bone marrow-derived macrophages, by assessing phagosomal recruitment of the lysosome-associated membrane protein 1 (LAMP-1) and intraphagosomal acidification. Whereas three out of six L. braziliensis strains impaired the phagosomal recruitment of LAMP-1, only the ML strain inhibited phagosome acidification to the same extent as the L. donovani strain that was used as a positive control. While decreased phagosomal recruitment of LAMP-1 correlated with higher LPG levels, decreased phagosomal acidification correlated with higher GP63 levels. Finally, we observed that the ability infect and replicate within host cells did not fully correlate with the inhibition of phagosome maturation. Collectively, our results revealed a diversity of strain-specific phenotypes among L. braziliensis isolates, consistent with the high genetic diversity within Leishmania populations.